2010
DOI: 10.1021/ja910547c
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Tunneling to Hopping Transport in Long, Conjugated Oligo-imine Wires Connected to Metals

Abstract: We report the electrical transport characteristics of conjugated oligonaphthalenefluoreneimine (ONI) wires having systematically varied lengths up to 10 nm. Using aryl imine addition chemistry, ONI wires were built from gold substrates by extending the conjugation length through imine linkages between highly conjugated building blocks of alternating naphthalenes and fluorenes. The resistance and current-voltage characteristics of ONI wires were measured as a function of molecular length, temperature, and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
352
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(394 citation statements)
references
References 76 publications
37
352
5
Order By: Relevance
“…The room-temperature current scales linearly with voltage in the low bias regime which is consistent as well with an ohmic hopping conduction (see Fig. 5a) 30,31 . In our experimental data, we can observe three distinct features of the temperaturedependent I-V traces of the devices with leaky AlO x barrier that are typical of amorphous organic layers with hopping transport 21 .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The room-temperature current scales linearly with voltage in the low bias regime which is consistent as well with an ohmic hopping conduction (see Fig. 5a) 30,31 . In our experimental data, we can observe three distinct features of the temperaturedependent I-V traces of the devices with leaky AlO x barrier that are typical of amorphous organic layers with hopping transport 21 .…”
Section: Discussionsupporting
confidence: 78%
“…5a). These two different regimes following a power law at low and high bias correspond to an ohmic conduction and a field emission regime, respectively 30,31 . The room-temperature current scales linearly with voltage in the low bias regime which is consistent as well with an ohmic hopping conduction (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Studies on various -conjugated molecules have been performed. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The molecules, with delocalized electrons due to sp 2 hybridized carbon atoms, exhibit a smaller energy gap between the highest occupied molecular orbital ͑HOMO͒ and the lowest unoccupied molecular orbital ͑LUMO͒. For -conjugated molecules longer than ϳ3 nm hopping conduction was observed.…”
Section: Electrical Characteristics Of Conjugated Self-assembled Monomentioning
confidence: 99%
“…The successful design and synthesis of these polymers linked by B-O [3][4][5], C-C [6,7], C-N [8], and C=N [9][10][11][12] bonds have been reported. Recent studies have shown that conjugated organic polymers (COPs) with extended π-conjugation possess high thermal stability and structure diversity [13][14][15].…”
Section: Introductionmentioning
confidence: 99%